Structure of separative dedekind groups - Kuzennyi, N. F.; Semko, N. N. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We describe groups such that all their subgroups that do not belong to a certain proper subgroup are normal. We also solve the separate problem of description of such groups with normal non-Abelian subgroups.